The struggle for power in colonial America, 1607-1776 - Nester, William R., 1956- (Lexington Books, 2017)
This study provides a broad examination of the overlapping conflicts and power struggles among the Indigenous population, colonists, and other European peoples that shaped the American colonies. The author analyzes the origins, development, and outcomes of such conflicts and their various cultural and political impacts.